ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DALAM LEARNING CYCLE 7E BERDASARKAN GAYA BELAJAR - Rosmaiyadi Rosmaiyadi (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This research aims to test the effectiveness of Learning Cycle 7E”, the influence of learning style against the students ability of critical thinking, the best learning style of the student is critical thinking ability and description of students’ mathematical critical thinking ability in each learning style. The methods used in this research was Mixed Design Model; the Sequential Explanatory Method. The subject of this research is grade VIII. The research instrument used is the TKBKM, learning style questionnaire and interview guidelines. The effectiveness of Learning Cycle 7E it can be seen from the aspect of completeness, obtained the result that the proportion of students who got a value KBKM greater than or equal with KKM=70 have exceeded 75%, while the average difference test of experiments class and control class were t-count=6,497>t-tabel=1,671. This shows that the average students’ mathematical critical thinking ability taught by Learning Cycle 7E more than average than students’ mathematical critical thinking ability taught with conventional learning. Learning styles affect the students’ mathematical critical thinking ability, this is retrieved based on the test results of the Kruskal Wallis with Asym value sig is 0.046<0.05. The visual learning style has the best ability of mathematical critical thinking. Each learning style has advantages and disadvantages on aspects of ability of critical thinking mathematically, thus causing each learning style has differences the ability of critical thinking mathematically too.